Vulval Elephantiasis: A Case Report - Harsh Mohan; Bhumika Bisht; Poonam Goel; Geeta Garg (Case Reports in Infectious Diseases)
Introduction. Elephantiasis is a chronic manifestation of filariasis; it commonly affects limbs, scrotum, and trunk. Females have lower incidence of filarial infection. Vulval elephantiasis due to filariasis is still rarer. It is difficult to make the diagnosis on histopathology alone, more so in view of the fact that the parasite is usually not identified in tissue sections. Identification of microfilariae in night samples of peripheral blood or seropositivity for filarial antigen is requisite for the correct diagnosis. Case Presentation. A young female presented with progressively increasing vulval swelling over a period of two years. The swelling was soft and measured 5×6 cm. Other possible differential diagnoses were excluded, and ancillary tests were performed to reach a conclusive diagnosis of vulval elephantiasis on histopathology. Conclusion. Vulval elephantiasis due to filariasis is rare. Its diagnosis on histopathology is more often by exclusion. High index of suspicion on microscopic findings and corelation with relevant diagnostic tests are required to reach the correct diagnosis.